EFFICACY AND SAFETY OF RHO KINASE INHIBITOR EYEDROPS FOR THE TREATMENT OF OPEN-ANGLE GLAUCOMA AND OCULAR HYPERTENSION: A LITERATURE REVIEW - Sahar Salim Saleh Alatas; Astrianda Nadya Suryono (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Reduction of intraocular pressure (IOP) is the only proven method to treat glaucoma. Studies on aqueous humor dynamics have contributed to our understanding of aqueous outflow mechanisms that have led to the discovery of new drugs from Rho Kinase Inhibitors (RKI). Aims: To evaluate the efficacy and safety of RKI for treating open-angle glaucoma (OAG) and ocular hypertension (OHT). Methods: Literature searching was conducted through PubMed, ScienceDirect, Google Scholar, and Springer Link. Search terms included: “Open Angle Glaucoma”, “Ocular Hypertension”, and “Rho Kinase Inhibitors”, which provides for Netarsudil (AR-13530), Ripasudil (K-115)